Evaluation of the coordination between eco-environment and socioeconomy under the “Ecological County Strategy” in western China: A case study of Meixian - Yi Yang (Elsevier, 2021)
Harmonious eco-environment and socioeconomic development is challenged by the difficulty of achieving sustainable development goals in rural areas in developing regions. Moreover, the exploratory strategy of the Ecological County Strategy and management practices of ecological restoration in these regions have not attracted sufficient academic attention. This study uses Meixian County as a case study. We use modified ecological footprint to characterize the ecological environment system of counties, and establish an evaluation index system that reflects the characteristics of counties’ socioeconomic development system. Based on the analysis of the dynamic characteristics of the per capita ecological footprint of Meixian, the grey correlation degree model and coupling degree model were used to analyze the key factors and the degree of coordination between the eco-environment and socioeconomy. The results show that the per capita ecological footprint of Meixian decreased from 0.5884 ha/cap to 0.4797 ha/cap from 2011 to 2016, the quality of the eco-environment has improved. The results of the grey correlation degree show that the ecological footprints of agricultural inputs and agricultural pollutants are important factors that restrict socioeconomic development. The local financial revenue (0.6898), per capita kiwifruit income (0.6842), and the coverage rate of pension insurance (0.7098) and medical insurance (0.6668) all have considerable effects on improving the eco-environment. The results of the coupling coordination degree show that the average annual growth rate of the coupling coordination between the eco-environment system and the economic system is 7.84%, which is in a coordinated or higher state. The average annual growth rate of the coupling coordination between the eco-environment and the social system is 15.25%, and the coordination level rose from imbalanced to highly coordinated state. This study confirms the positive role of the Ecological County Strategy in promoting the coordinated development of counties, and provides beneficial experience for counties in developing regions to improve the coordination between eco-environment and socioeconomy on the basis of ecological carrying capacity.